Antibiotics on the rise: Google trends as a monitoring tool in India - Somagutta, Manoj Reddy; Pormento, Maria K. L.; Hange, Namrata; Iloeje, Obumneme J.; Jain, Molly S.; Ghazarian, Klodin; Sasidharan, Nayana; Sajjanagandla, Gouthami; Mahadevaiah, Ashwini; Mahmutaj, Greta; Hanan, Saad (International Journal Of Community Medicine And Public Health, 2021)
Coronavirus disease 2019 (COVID-19) pandemic has put enormous strains on health care and public sector resources globally, especially in low- and middle-income countries. The extensive and often inept use of antibiotics during the pandemic is suspected. Data from Google trends (GT) enables the assessment of Google users' interest in a specific topic. A strong correlation between active COVID-19 cases and GT search terms of antibiotics (r=0.90) azithromycin (r=0.96) and doxycycline (r=0.93) were noticed with p<0.05. However, hydroxychloroquine (r=0.21) was not significant. Further investigation is needed to determine GT as a possible adjunctive monitoring tool for antibiotic use and formulate drug resistance patterns in India.